2006
DOI: 10.1111/j.1742-7924.2006.00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Assertiveness affecting burnout of novice nurses at university hospitals

Abstract: Aim: This prospective cohort study aimed to clarify the relationship between the level of assertiveness and the incidence of burnout in novice nurses in their first year at university hospitals and to obtain indices of assertion training in order for them to avoid burnout. Methods: The subjects were 1203 novice nurses working at 20 university hospitals in Japan who gave informed consent to participate in this research. The questionnaires were completed by 949 novice nurses in June 2003, and they were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 27 publications
3
43
0
1
Order By: Relevance
“…Furthermore, the mean total RAS score improved from −14.2 to −8.9, which corresponds to meaningful improvement from outside the optimal range (<−10) to inside the optimal range (≥−10). According to a previous prospective cohort study (Suzuki et al., ), to avoid burnout, the ideal target value for RAS scores is thought to be in the range of −10 to 10 (optimal range).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the mean total RAS score improved from −14.2 to −8.9, which corresponds to meaningful improvement from outside the optimal range (<−10) to inside the optimal range (≥−10). According to a previous prospective cohort study (Suzuki et al., ), to avoid burnout, the ideal target value for RAS scores is thought to be in the range of −10 to 10 (optimal range).…”
Section: Discussionmentioning
confidence: 99%
“…Assertiveness is typically defined in terms of the honest and legitimate expression of one's personal opinions, needs, wants and feelings without denying or violating the rights of the others (Alberti & Emmons, ). Previous studies have indicated that poor assertiveness in nurses is related to reality shock, burnout, intention to leave and less commitment to work (Azuma & Suzuki, ; Itomine, Suzuki, Kanoya, & Sato, ; Suzuki, Kanoya, Katsuki, & Sato, ; Suzuki, Kanoya, Kitaoka‐Higashiguchi, & Sato, ; Suzuki et al., ). Assertive communication also enables nurses to build effective team relationships because collaboration with other health care professionals requires both a high level of assertiveness and cooperation (Boone, King, Gresham, Wahl, & Suh, ).…”
Section: Introductionmentioning
confidence: 99%
“…Low levels of assertiveness are associated with high risk for burnout. However, Suzuki et al (2006) stress the need for effective and culturally sensitive assertiveness training as new nurses transition to professional practice.…”
Section: Turnovermentioning
confidence: 98%
“…Burnout and turnover intention may also be related to effective communication. Researchers have investigated the influence of assertiveness on burnout among new nurses (Suzuki, Kanoya, Katsuki, & Sato, 2006). According to Alberti and Emmons (as cited in Suzuki et al, 2006), assertiveness is perceived as the ability to express your rights and feelings while respecting the rights, feelings, and ideas of others.…”
Section: Turnovermentioning
confidence: 99%
“…According to one researcher, female healthcare workers tend to report higher levels of burnout. 33 The study hypotheses for the demographic values were as follows: 33 Hypothesis 1 (H1) of this study investigated whether there's an association between gender and burnout.…”
Section: Positive or Negative Connotation?mentioning
confidence: 99%